Neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio as predictive markers in hepatoblastoma - Xie, Tan; Hou, Dongliang; Wang, Jiaxiang; Zhao, Song (Frontiers in Pediatrics, 2023)
Background: The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been presented to be a prognostic indicator in several cancers. We were supposed to evaluate the prognostic role of such inflammatory markers in hepatoblastoma (HB). Methods: Total of 101 children, diagnosed with hepatoblastoma between January 2010 and January 2018, were enrolled before treatment in the study. The clinicopathological parameters, and outcomes were collected through laboratory analyses and patient follow-up. The association between NLR, PLR, and clinicopathological characters were analyzed with Wilcoxon test, Chi-Squared test, Kaplan-Meier, Log-rank and Cox regression analyses. Results: NLR and PLR were significantly elevated in HB patients (P < 0.001), and related to age (P < 0.001), risk stratification system (P < 0.001), and pretreatment extent of disease (P < 0.0001). NLR was significantly related to alpha-fetoprotein (P = 0.034) and lactate dehydrogenase (P = 0.026). The 3-year overall survival (OS) and event-free survival (EFS) were poor in the high-NLR group (OS: 44.3% vs 90.3%, P < 0.0001, EFS: 38.6% vs 80.6%, P = 0.0001). The 3-year OS and EFS were poor in the high-PLR group (OS: 49.1% vs 68.8%, P = 0.016, EFS: 39.6% vs 64.6%, P = 0.0117). The multivariate analysis suggested that NLR (HR: 11.359, 95% CI: 1.218-105.947; P = 0.033) and risk stratification (HR: 44.905, 95% CI: 2.458-820.36; P = 0.01), were independent predictors of OS. Conclusions: Our research showed that elevated NLR and PLR were the poor prognostic factors in HB patients before treatment. The NLR was an independent prognostic factor for OS.